In Silico of AMHRII Receptor Binding and Toxicity Prediction of Clitoria ternatea - Kurniawati, Erna Yovi; Mahati, Endang; Zaw Myo Hein (Window of Health : Jurnal Kesehatan, 2024)
Clitoria ternatea compounds show significant potential as herbal drug candidates for polycystic ovary syndrome (PCOS) through improving anti-Müllerian hormone (AMH) parameters. This study aims to evaluate the potential of these compounds in binding to AMHRII receptors using an in silico approach. Several compounds, baicalein, isorhamnetin, and malvidin, showed high binding affinity towards AMHRII receptors, approaching or even surpassing some control drugs. These compounds have favorable toxicity profiles, with high LD50s, suggesting low toxicity and high safety potential for therapeutic use. Some compounds, such as isorhamnetin, termination, petunidin, malvidin, cyanidin, luteolin, and protocatechuic acid, have an unfavorable number of hydrogen donors, as does gallic acid, which has an unfavorable number of hydrogen acceptors. The development of technologies that improve bioavailability and pharmacokinetics can overcome these challenges. Further studies in vivo are needed to confirm the effectiveness and safety of these compounds in potential clinical therapies and develop innovative herbal therapies for Clitoria ternatea-based PCOS.